THE SITUATION OF HEALTH HUMAN RESOURCES IN DISTRICT HOSPITALS IN THAI NGUYEN PROVINCE (Vietnam Journal of Community Medicine, 2021)
This study aims to analyze and evaluate the situation of health human resources in district hospitals in Thai Nguyen province in the period of 2017-2019, thereby proposing solutions to develop health human resources in these hospitals in the period 2020-2025. Solutions are to adequately meet the quality of health human resources, rationally structured and distributed, contribute to improving the quality of health and people's health, towards effective, equity and development
Keywords: Healthcare; health human resources, district hospital, Thai Nguyen province